Competition–cooperation interplay during multifirm technology coordination - Ranganathan, Ram; Ghosh, Anindya; Rosenkopf, Lori (Strategic Management Journal, 2018)
[Research Summary: We examine how competitive tensions and cooperative motivations together shape firms’ interactions and group-level outcomes during technology coordination activities in multifirm settings. Analyzing the communication and voting behavior of 115 firms across three subcommittees of a computing industry technology standards-setting organization over 14 years, we find that existing product-market positions influence how firms with highly overlapped technological resources differ in their interactions: when their product-markets are more competitive, they exhibit greater support for the emerging standard, as evidenced by positivity and certainty of interaction tone; but when they possess a broader array of complementary products, support is tempered. At the subcommittee level, after accounting for aggregate competitive tensions in prior interactions, heterogeneity in both firms’ relational influence as well as their prior multiparty experience improve consensus. Managerial Summary: In innovation ecosystems, competing firms are often obligated to collaborate with each other in large multifirm forums to develop the technical standards that enable interoperability between their products. We show how the networks of technical and commercial relationships between firms shape such standards activities in two steps. First, firms who share many common technology interests with others communicate their support for new standards more vigorously when they participate in more competitive product-markets, but less vigorously when they possess more complementary products. Second, communities find broader support for standards when there is greater imbalance across both firms’ prior collaborative experiences as well as their pattern of relationships. We demonstrate these results in a study of 115 firms participating in computer peripherals standards development over 14 years.]